Kuna domowa (Martes foina) na kampusie Szkoły Głównej Gospodarstwa Wiejskiego (SGGW) w Warszawie: sezonowe i dobowe wykorzystanie schronień antropogenicznych oraz skład pokarmu - Kubich, Jakub; Gryz, Jakub; Jasińska, Karolina; Krauze-Gryz, Dagny (Leśne Prace Badawcze, 2024)
The aim of the study was to characterise the occurrence of stone martens on the SGGW campus in Warsaw, their seasonal and diurnal use of buildings as hiding places and their food composition. For this purpose, 22 camera traps were used, twelve of which were placed inside and ten outside buildings. Data were collected from January to December 2022. We also collected marten faeces found inside buildings and analysed them to determine the main food categories. Martens (131 observations) used the attics of SGGW buildings as hiding places from January to May and were absent from September to December. They were most active in the evening and at night, with activity peaking between 3:00 and 4:00 am. Outside buildings, martens were recorded sporadically. Martens fed mainly on plant food (fruit), somewhat less frequently on small mammals and even less frequently on birds. Invertebrates made up only a small part of their diet. The absence of martens in the buildings surveyed in autumn and early winter, although they are present on campus during this time, could indicate that they also use other buildings that were not surveyed. Martens use the buildings not only for sleeping, but also for their activities. When foraging, they probably use the numerous fruit trees and shrubs in the park part of the campus and in the backyards of the surrounding houses.